15-year experience with rotavirus vaccination in Mexico: a systematic literature review. Issue 10 (3rd October 2021) - Guzman-Holst, Adriana; Ortega-Barria, Eduardo; Flores, Ángel Alexis; Carreño-Manjarrez, Roberto; Constenla, Dagna; Cervantes-Apolinar, Maria Yolanda
ABSTRACT: A systematic review was conducted in Mexico to consolidate and evaluate evidence after 15 years of rotavirus vaccination, according to the National Immunization Program. Five databases were screened to identify published articles (January 2000–February 2020) with evidence on all clinical and epidemiological endpoints (e.g. immunogenicity, safety, efficacy, impact/effectiveness) of rotavirus vaccination in Mexico. Twenty-two articles were identified (observational studies including health-economic models: 17; randomized controlled trials: 5). Fourteen studies evaluated a human attenuated vaccine (HRV), four studies evaluated both vaccines, and only two evaluated a bovine-human reassortant vaccine, with local efficacy data only for HRV. Local evidence shows vaccines are safe, immunogenic, efficacious, and provide an acceptable risk-benefit profile. The benefits of both vaccines in alleviating the burden of all-cause diarrhea mortality and morbidity are documented in several local post-licensure studies. Findings signify overall benefits of rotavirus vaccination and support the continued use of rotavirus vaccine in Mexico.